Performing against the odds: developmental trajectories of children in the EPPSE 3-16 study - Siraj-Blatchford, I; Mayo, A; Melhuish, E; Taggart, B; Sammons, P; Sylva, K (Department for Education, 2011)
This study explores how risks and protective factors shape children's learning and why it leads to academic resilience for some, not others.